Arahan Pengembangan Fungsi Kawasan Pelabuhan Rakyat sebagai Kawasan Pelabuhan Wisata di Desa Boroko Kabupaten Bolaang Mongondow utara Sulawesi utara - Muhammad Zaki (LOSARI : Jurnal Arsitektur Kota dan Pemukiman, 2016)
Activity arrangement of buildings and the environment is one important part of the effort to create an integrated spatial planning,by creating new activities, environmental quality, targeted settlements , and the region as part of an urban space. The purpose of the development of port functions is to develop the potential of the area to the shore in the village Boroko Bolaang Mongondow Regency with the development concept faslitas and infrastructure that are customized to the character and condition of community environment and consider the principles stats sustainable environment as well as to integrate the function of settlement , transport infrastructure and activities to bridge various commercial activities, public facilities and social facilities in the province traffic lane. Methods and Function Development Tutorial This port is done using descriptive method and is intended to facilitate the activities of tourist beaches and islands around the harbor tourist villages such Boroko Batu Pinagut Beach, Damar Island, Ayer Belanda, Tanjung Dulang Beach. The final results of this study give birth to new ideas and with regional development approach guided by analysis and concept design direction as a travel destination development Bolaang Mongondow District.